The modern development of the hospitality industry in the Republic of Kazakhstan - Beyzhanova, A. T.; Belgozhakyzy, M.; Shurenov, N. B. (Journal of Economic Research & Business Administration, 2016)
Currently, the economic potential of the development of the hospitality industry is recognized as one of the most promising sectors. Hospitality is an important component of the tourism business. A tourism play a key role in the global economy as a complex, global national product, which provides 1 10 of the national product. Currently, every fifteenth employee working in the hospitality industry. These figures in the tourism industry, including hotel industry is characterized as the functioning of economic efficiency.